1951
DOI: 10.1111/j.1365-2621.1951.tb17411.x
|View full text |Cite
|
Sign up to set email alerts
|

FACTORS INFLUENCING THE STABILITY OF THIAMINE DURING HEAT STERILIZATIONa

Abstract: The effect of heat and certain environmental factors on thiamine stability has been the subject of several comprehensive investigations (2, 3, 8,9,10,12,13, 14,16,17, 18,19). There is good evidence that in pure thiamine solutions the destruction by heat is primarily a hydrolytic cleavage to give pyrimidine and thiazole derivatives (20), and that the reaction rate may be expressed by the conventional equation for a first-order reaction. The effect of p H on the rate of thiamine destruction in pure solutions has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Mashing temperatures were investigated for their effect on the release of thiamine and riboflavin vitamers into the wort. This was performed by adding 50 g of 22 mm ground Pilsner malt to 350 mL of distilled water at varying temperatures (45,55,65 and 72°C) in a 600 mL stainless steel mashing beaker. These mashes were then maintained at their various temperatures for 1 h, while samples were taken and the mashes stirred every 10 min.…”
Section: Effect Of Mashing Temperatures On Vitamin Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Mashing temperatures were investigated for their effect on the release of thiamine and riboflavin vitamers into the wort. This was performed by adding 50 g of 22 mm ground Pilsner malt to 350 mL of distilled water at varying temperatures (45,55,65 and 72°C) in a 600 mL stainless steel mashing beaker. These mashes were then maintained at their various temperatures for 1 h, while samples were taken and the mashes stirred every 10 min.…”
Section: Effect Of Mashing Temperatures On Vitamin Releasementioning
confidence: 99%
“…Since malt is the main ingredient after water in wort production it is likely that mashing conditions will greatly affect the solubilization and extraction of these vitamins. It is also likely that the boiling step used to sterilize the wort may lead to a decrease in thiamine content owing its heat instability . Other factors such as the denaturation of proteins (resulting in the liberation and/or destruction of protein‐bound vitamins) at elevated temperatures, the use of processing aids and the addition of hops may also impose either a positive or a negative effect on the final vitamin content of wort.…”
Section: Introductionmentioning
confidence: 99%
“…5). Bendix et al (1951) showed the effect of high pH on increasing the destruction of thiamine in (Fernandez, 1984). (0) Phosphate buffer+glycerol, a, = 0.95 (Fernandez, 1984). tomatoes and lima beans.…”
Section: P Hmentioning
confidence: 99%
“…Although this study investigated thiamine stability in simple aqueous solutions at higher thiamine concentrations than are often found in food products, understanding the fundamental reaction mechanisms of thiamine degradation can be used to predict the responses in a variety of food formulations and vitamin supplements. Thiamine has been reported to be more stable in food systems than in buffer systems, and thiamine degradation has been shown to both deviate from and to follow first-order reaction kinetics in food products due to interactions with food ingredients [ 31 , 41 , 45 ]. Regardless of order of reaction, certain components in food are known to affect the stability of thiamine.…”
Section: Resultsmentioning
confidence: 99%